The Analog Rice from Gembili Tubers which Contain Various of Benefits: An overview - Iriana, Tumiar; kusumayanti, Heny (Universitas Airlangga, 2023)
Gembili (Dioscorea esculenta), has very good potential, one of which is that the tubers produced have many benefits, apart from being believed to contain high carbohydrates, gembili also contain calcium, potassium, iron and vitamin B6. Apart from being used as a simple food, gembili tubers can be used as an analogue of rice. This review aims to examine and find out the various benefits of gembili tubers, the combination of various agricultural ingredients in producing analog rice and the resulting characteristics. The method of making analog rice is done by extruder. Test how many studies include proximate tests, antioxidants, calcium, levels of fiber and amino acids. Based on several studies of analog rice that made from gembili with tubers 78%, protein content 8%, water content 7.9%, ash content 2-3.5%, fat content 0.5-1.2%, antioxidants 6162 ppm, fiber crude 10% and calcium 1.52%, each. The characteristics of rice is shape, texture, color, and taste to can be accepted by the community. Analog rice can be used as a substitute for rice.